Permanent education in patient assistance with HIV: an integrating review (Research, Society and Development, 2020)
Human immunodeficiency virus (HIV) infection remains a relevant social issue worldwide. Data still point significant values in the numbers of new cases. A major challenge is maintaining adherence to treatment, as several reasons may contribute to its abandonment. Pharmaceutical professionals periodically dispense drugs to such patients and have the opportunity to accompany and guide them and may contribute to the care provided to such people. For this, it is essential that they have knowledge of the subject and feel safe to advise. The education of this professional on the subject is relevant, needing to be constant since there are always updates in this area. Objective: This article aimed to analyze what the most recent literature on the pharmacy service provided to people living with HIV / AIDS (PLHA) says and its relationship with continuing health education. Methodology: For this, an integrative literature review was performed through the Medline, Lilacs, Cinahl, Scopus and Web of Science databases. Results: From the 125 articles found 03 were selected, after applying the exclusion criteria, for complete reading and synthesis. All were in English being found: 1 from Medline and 2 from Web of Science. Of these, 2 were published in 2014 and 1 in 2018. Discussion: The articles point out that many pharmacists do not feel competent to guide and advise on HIV prophylaxis as well as news about treatment and that some have never received training on the subject. It is suggested in these articles that education on HIV / AIDS, its treatment and prophylaxis should be applied to such health professionals, since they are located in a strategic location and are easily accessible to the population. The curricula of undergraduate and residency courses in pharmacy do not include enough content on the subject, being quite superficial what can contribute to the insecurity of professionals. HIV is among the ten health priorities of the World Health Organization and also in the National Agenda of Priority in Research of the Ministry of Health (ANPPMS) with constant research and updates on its theme as treatment and prevention. (UN, 2019) (Brazil, 2018). It is essential that there are forms of education and updating aimed at professionals in this area. Continuing education, continuing education and in-service education, although they are processes that are based on different methodological principles, are characterized by the continuity of educational actions, which can be used to develop skills and competences, strengthening the work performed. Conclusion: The literature does not speak specifically about the continuing education of pharmacists who work with PLHA, being valid research on the subject. However, the selected articles show that there is a need for education on the subject and the recognition of professionals about this need. Thus, it is concluded that more needs to be invested in HIV / AIDS content in pharmacy undergraduate curricula, and that continuing health education along with continuing education for such professionals can fill existing knowledge gaps and contribute for skills development. It is suggested in this article that permanent health education be carried out with all staff working in the pharmacy sector (pharmacists, technicians, assistants), which will enrich the discussions and learning of the group, bringing greater confidence to both professionals. as for patients, even reflecting on the improvement of the treatment adherence process and, consequently, on the control of the HIV / AIDS epidemic.